Role of TLR4 in Neutrophil Dynamics and Functions: Contribution to Stroke Pathophysiology - Durán-Laforet, Violeta; Peña-Martínez, Carolina; García-Culebras, Alicia; Cuartero, María Isabel; Lo, Eng H.; Moro, María Ángeles; Lizasoain, Ignacio (Frontiers in Immunology, 2021)
Background and purpose: The immune response subsequent to an ischemic stroke is a crucial factor in its physiopathology and outcome. It is known that TLR4 is implicated in brain damage and inflammation after stroke and that TLR4 absence induces neutrophil reprogramming toward a protective phenotype in brain ischemia, but the mechanisms remain unknown. We therefore asked how the lack of TLR4 modifies neutrophil function and their contribution to the inflammatory process. Methods: In order to assess the role of the neutrophilic TLR4 after stroke, mice that do not express TLR4 in myeloid cells (TLR4loxP/Lyz-cre) and its respective controls (TLR4loxP/loxP) were used. Focal cerebral ischemia was induced by occlusion of the middle cerebral artery and infarct size was measured by MRI. A combination of flow cytometry and confocal microscopy was used to assess different neutrophil characteristics (circadian fluctuation, cell surface markers, cell complexity) and functions (apoptosis, microglia engulfment, phagocytosis, NETosis, oxidative burst) in both genotypes. Results: As previously demonstrated, mice with TLR4 lacking-neutrophils had smaller infarct volumes than control mice. Our results show that the absence of TLR4 keeps neutrophils in a steady youth status that is dysregulated, at least in part, after an ischemic insult, preventing neutrophils from their normal circadian fluctuation. TLR4-lacking neutrophils showed a higher phagocytic activity in the basal state, they were preferentially engulfed by the microglia after stroke, and they produced less radical oxygen species (ROS) in the first stage of the inflammatory process. Conclusions: TLR4 is specifically involved in neutrophil dynamics under physiological conditions as well as in stroke-induced tissue damage. This research contributes to the idea that TLR4, especially when targeted in specific cell types, is a potential target for neuroprotective strategies.